RELATIONSHIP BETWEEN DENTAL AND BIOCHEMICAL FACTORS PROBLEMS ASSOCIATED WITH DIABETIC PATIENTS TYPE 2 IN A SAMPLE OF THE POPULATION OF METROPOLITAN LIMA - Arias Caycho, Luis Clever (2016)
Objective. Determine the relationship between problems oral and them factors biochemical associated to patients with diabetes type 2.Materials and methods. Cross-sectional, descriptive study carried out above. 37 type II diabetic patients ranging from 40 - 71 years. Be developed surveys clinical, is valued measures anthropometric and pressure blood. Biochemical analyses included assessment of glucose, cholesterol, triglycerides and insulin levels. The prevalence of caries was evaluated with the index DMFT.Results. Them results found were the 80,6% HTA altered high, only the 20% IMC normal, State of hyperglycemia (half of 143 mg %,p = 0,001), not there was pictures of resistance to the insulin, hypertriglyceridemia (half 216,62 p = 0,001) and hypercholesterolemia (half 207,59 p = 0,001); in the evaluation dental is found 46% xerostomia, the 1.27% canker sores, the 32% bleeding oral, the 11%language urolithiases, the 16% hypertrophy of glands salivary and 22% meant b